A Study on Mandarin Proficiency and Multidimensional Poverty in Ethnic Areas - Wang, Lucong (JOURNAL OF ADVANCES IN LINGUISTICS, 2021)
To study the role of language in anti-poverty, based on the theory of multidimensional poverty and the economic value of language, this paper analyzes the correlation between Mandarin proficiency and multidimensional poverty in ethnic minority areas by using CFPS data from 2010 to 2018. The regression results show that the improvement of Mandarin proficiency is beneficial to solve multidimensional poverty problems. The endogenetic analysis and robustness test are carried out, and the conclusion is consistent with the baseline regression. Further, the influence of language ability on different samples is analyzed. The study shows that Mandarin proficiency has a greater influence on male, 18-28 and 29-50 years old, high poverty groups and non-agricultural workers.